Safety and Ethics in the Global Workplace: Asymmetries in Culture and Infrastructure - Lorenzo, Oswaldo (Journal of business ethics, 2010)
This study described and analysed the circumstances surrounding a fatal car accident involving personnel of a multinational corporation in a developing country. For some companies, road accidents are the leading cause of work-related fatalities in developing countries. This reality highlights the ethical dilemmas encountered in a global workplace. Questions as to how a company addresses safety concerns outside the standard work environment, the ethics of operating in a risky environment and the requirements for international consistency in compensation standards for loss of life were addressed. The authors argued that multinational companies should localize health and safety practices to address the important asymmetries between different regions of the world regarding social, cultural and infrastructural issues. Furthermore, the authors analysed the leadership role that should be played by multinational companies to help and support national governments to reduce traffic fatalities in developing countries. From this perspective, the article represents a contribution for the body of knowledge dealing with the business–society relations. The authors used an action research approach to address these issues, both in response to the particular incident and to contribute to the body of research in this field.